Kirke og stat i 1600-tallet - Petersen, Klaus; Rode, Hans-Henrik (Kirkehistoriske Samlinger, 1995)
The present paper offers an analysis of the relationship between state and church in the sixteenth century in Denmark. The interaction between the two institutions reflects a number of convulsions which existed in the society at that time. The paper draws special attention to the financial troubles of the state and the emergence of the central state. Moreover religious affairs played a determining role in foreign politics up to the Peace of Westphalia, 1648. In the period at issue ecclesiastical activities were gradually made subject to regulations and by degree more duties were placed within the realms of the church. Throughout the entire period the state was the stronger force whereas the Reformation had stripped the church of its powerful position. The increase in regulations showed most visibly in regards to the ecclesiastical discipline which subjugated both clergy and laity to stricter disciplinary measures. The underlying reason for the ecclesiastical discipline were religious motives and the intention of strenghtening social control. The church served as a means to legitimize the secular autorities, particularly during the foreign political crisis which stemmed from the military defeat in 1629 of King Christian IV. As early as the fifteenth century parish priests had performed minor administrative tasks in relation to those services dealing with the poor and the beggars. In 1645, however, those services were noticeably extended. The priests were now ordered to keep the official books of administration which would serve as basis for imposition of taxes. During the absolute monarchy the priests were also little by little made responsible for the actual collection of taxes. With the advent of the absolute monarchy in 1660 statepower was defined in clear terms, thus enabling a coherent and concise regulation of the relationship between state and church as witnessed in the legislation af the absolute monarch. Before 1685 legislation concerning the church was fragmentary and many points of policy were decided ad hoc. Still, a fundamental revision of the hitherto legislation did not occur. The absolute monarchy merely assembled law and practice in respect to the church of the years prior. The Reformation left a power-gap between state and church. This gap was gradually filled in by the state which subdued the church. The priests became a class of civil servants loyal to the state. With the consolidation of absoulte monarchy this slow transition was eventually accomplished.